Favorable Outcome of an Exclusively Posttransplant Prophylactic Strategy After Heart Transplantation in Recipients With High Immunological Risk. Issue 7 (July 2019) - Coutance, Guillaume; d'Orio, Virginie; Belin, Lisa; Bréchot, Nicolas; Saheb, Samir; Lebreton, Guillaume; Bouglé, Adrien; Rouvier, Philippe; Gautreau, Chantal; Ouldammar, Salima; Chamillard, Xavier; Huot, Mélanie; et al.
Abstract : Background: Management of the increasing number of sensitized heart transplant candidates has become a recurrent issue. Rather than using pretransplant desensitization therapies, we used a posttransplant prophylactic strategy. Our aim was to describe outcomes in transplant recipients with preformed donor-specific anti-HLA antibodies (pfDSA) managed with this strategy. Methods: A posttransplant protocol was applied to patients transplanted with pfDSA, consisting of perioperative management of DSA (polyvalent immunoglobulins +/− perioperative plasmapheresis sessions, according to DSA level, as well as induction therapy) and systematic treatment of subsequent antibody-mediated rejection (AMR), even when subclinical. We performed a retrospective analysis of this prospective protocol. The study included all consecutive first recipients of a noncombined heart transplant performed between 2009 and 2015 at our center. The primary endpoint was all-cause mortality. Secondary endpoints included primary graft dysfunction, early posttransplant bleeding, rejection, and cardiac allograft vasculopathy-free survival. Results: A total of 523 patients were studied, including 88 (17%) and 194 (37%) transplanted with DSA mean fluorescence intensity (MFI) of 500 to 1000 and greater than 1000, respectively. The median follow-up period was 4.06 years. Survival was not significantly different between groups. Rejection-free survival was worse in patients with pfDSA MFI >1000, evidenced by a fourfold increase in the risk of antibody-mediated rejection. The incidence of primary graft dysfunction and cardiac allograft vasculopathy-free survival did not significantly differ between groups. Perioperative plasmapheresis increased the risk for transfusion of packed red blood cells. Conclusions: This exclusively posttransplant prophylactic strategy achieved favorable outcomes in heart transplant recipients with pfDSA. Abstract : Supplemental Digital Content is available in the text.